The multiplication of the expression (x² + 3x + 2) (2x² + 3x + 1) is 2x⁴ + 9x³ + 14x² + 9x + 2
<h3>Multiplication</h3>
(x² + 3x + 2) (2x² + 3x + 1)
= 2x⁴ + 3x³ + x² + 6x³ + 9x² + 3x + 4x² + 6x + 2
= 2x⁴ + 3x³ + 6x³ + x² + 9x² + 4x² + 3x + 6x + 2
= 2x⁴ + 9x³ + 14x² + 9x + 2
Learn more about multiplication:
brainly.com/question/10873737
#SPJ1
Answer:
y/(x - 10)
Step-by-step explanation:
The quantity is x minus ten, which means that it is (x - 10)
y divided by the quantity = y/(x - 10)
~
Answer:
simple. y=x+2
Step-by-step explanation:
:) ======
Answer is (24,-24)
Explanation:
Dilation centered at the origin multiplies each coordinate by the dilation factor.
image= 4(6,-6)
image= (24,-24)
Step-by-step explanation:
3e <= 6
e <= 2 (divide 3 on both sides)
The e-values that satisfy the inequality are:
e = 1 and e = 2.